Predictors of right subclavian artery tortuosity in trans-radial coronary angiography access - Ermawan, Romi; Pintaningrum, Yusra; Rahmat, Basuki; Putra, AASM Meiswaryasti; Indrayana, Yanna (Heart Science Journal, 2025)
BACKGROUND: Trans-radial access has become the new standard and is increasingly in demand in coronary angiography. However, this method can fail due to tortuosity of the right subclavian artery. OBJECTIVES: This study aims to identify the predictors of right subclavian artery tortuosity. METHODS: This retrospective case-control study was conducted at two of the largest hospitals in West Nusa Tenggara, Indonesia. All research data were obtained from secondary sources, including video recordings of coronary angiographies, angiography reports, and patient medical records. Predictors included age, gender, smoking, height, body mass index, hypertension, diabetes mellitus, systolic and diastolic blood pressure, and random blood sugar. RESULTS: The study involved 80 subjects, divided into right subclavian artery tortuosity and normal group, with 40 subjects each. The prevalence of tortuosity was 8.1%, while the success rate of trans-radial access was 70.0%. Four significant predictors were identified: smoking (adjusted OR 0.26; p = 0.019), hypertension (adjusted OR 4.83; p = 0.020), diastolic blood pressure (adjusted OR 1.05; p = 0.044), and body mass index (adjusted OR 1.16; p = 0.035). The optimal cutoff points were determined to be a body mass index of ≥ 24.4 (sensitivity 60.0%; specificity 60.0%; p = 0.006; AUC = 0.665) and diastolic blood pressure of ≥ 78.5 mmHg (sensitivity 67.5%; specificity 67.5%; p = 0.002; AUC = 0.685). CONCLUSION: This study has identified smoking, hypertension, diastolic blood pressure, and body mass index as significant predictors of right subclavian artery tortuosity in trans-radial coronary angiography access.